Trans regulation of the phosphoenolpyruvate carboxykinase (GTP) gene, identified by deletions in chromosome 7 of the mouse. - Loose, D S (1986)
Livers from newborn mice homozygous for either one of the lethal deletions c14CoS or c3H in chromosome 7 have drastically reduced levels of cytosolic phosphoenolpyruvate carboxykinase (GTP) [GTP:oxaloacetate carboxy-lyase (transphosphorylating), EC 4.1.1.32] activity when compared with normal littermates. The structural gene for the enzyme maps on chromosome 2 and appears intact and not grossly rearranged in deletion homozygotes. These mice also have negligible levels of hepatic mRNA encoding this enzyme. Studies of the transcription rate of the gene showed that it was reduced to 25-50% of normal in hepatic nuclei obtained from mice homozygous for either deletion. We suggest that, in addition to the reduction in the level of transcription, the deletions in chromosome 7 may also cause alterations in messenger stability, processing, or transport from the nucleus.